Rapid prototyping of PMMA-based microfluidic spheroid-on-a-chip models using micromilling and vapour-assisted thermal bonding - Monieb A. M. Ahmed; Klaudia M. Jurczak; N. Scott Lynn; Jean-Paul S. H. Mulder; Elisabeth M. J. Verpoorte; Anika Nagelkerke (Scientific Reports, 2024)
Abstract The application of microfluidic devices as next-generation cell and tissue culture systems has increased impressively in the last decades. With that, a plethora of materials as well as fabrication methods for these devices have emerged. Here, we describe the rapid prototyping of microfluidic devices, using micromilling and vapour-assisted thermal bonding of polymethyl methacrylate (PMMA), to create a spheroid-on-a-chip culture system. Surface roughness of the micromilled structures was assessed using scanning electron microscopy (SEM) and atomic force microscopy (AFM), showing that the fabrication procedure can impact the surface quality of micromilled substrates with milling tracks that can be readily observed in micromilled channels. A roughness of approximately 153 nm was created. Chloroform vapour-assisted bonding was used for simultaneous surface smoothing and bonding. A 30-s treatment with chloroform-vapour was able to reduce the surface roughness and smooth it to approximately 39 nm roughness. Subsequent bonding of multilayer PMMA-based microfluidic chips created a durable assembly, as shown by tensile testing. MDA-MB-231 breast cancer cells were cultured as multicellular tumour spheroids in the device and their characteristics evaluated using immunofluorescence staining. Spheroids could be successfully maintained for at least three weeks. They consisted of a characteristic hypoxic core, along with expression of the quiescence marker, p27kip1. This core was surrounded by a ring of Ki67-positive, proliferative cells. Overall, the method described represents a versatile approach to generate microfluidic devices compatible with biological applications.